Efficiency Wages in Cournot-Oligopoly - Marco de Pinto; Laszlo Goerke (Institute of Labor Economics (IZA), 2019)
In a Cournot-oligopoly with free but costly entry and business stealing, output per firm is too low and the number of competitors excessive, assuming labor productivity to depend on the number of employees only or to be constant. However, a firm can raise the productivity of its workforce by paying higher wages. We show that such efficiency wages accentuate the distortions occurring in oligopoly. Specifically, excessive entry is aggravated and the welfare loss due to market power rises.
Keywords: D43; J31; L13; 330; oligopoly; efficiency wages; excessive entry; welfare